2014
DOI: 10.1111/zoj.12142
|View full text |Cite
|
Sign up to set email alerts
|

The adductor mandibulae muscle complex in lower teleostean fishes (Osteichthyes: Actinopterygii): comparative anatomy, synonymy, and phylogenetic implications

Abstract: Bony fishes of the morphologically diverse infraclass Teleostei include more than 31 000 species, encompassing almost one‐half of all extant vertebrates. A remarkable anatomical complex in teleosts is the adductor mandibulae, the primary muscle in mouth closure and whose subdivisions vary in number and complexity. Difficulties in recognizing homologies amongst adductor mandibulae subdivisions across the Teleostei have hampered the understanding of the evolution of this system and consequently its application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 150 publications
(549 reference statements)
2
47
0
2
Order By: Relevance
“…It is estimated that almost three-quarters of the total morphological information related to phylogenetic reconstruction is related to skeletal features (Wiley & Johnson, 2010). Datovo & Vari (2014) in a comprehensive review of morphological features used in fi h systematics, found a similar predominance of osteological characters (74%) in relation to other sets of data. According to those authors, 6% corresponded to myology, 5% to splanchnology, 14% to other morphological characters (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…It is estimated that almost three-quarters of the total morphological information related to phylogenetic reconstruction is related to skeletal features (Wiley & Johnson, 2010). Datovo & Vari (2014) in a comprehensive review of morphological features used in fi h systematics, found a similar predominance of osteological characters (74%) in relation to other sets of data. According to those authors, 6% corresponded to myology, 5% to splanchnology, 14% to other morphological characters (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…The pars rictalis forms the ventro‐lateral portion, the pars malaris forms the dorso‐lateral portion, and the pars stegalis forms the medial portion. In some taxa, including Esox , the rictalis and malaris form a compound facial segment, the ricto‐malaris (Datovo & Vari, ). In Anguilla , the rictalis and malaris segments share a common origin, but are divided anteriorly into distinct parts (Datovo & Vari, ), and so are discussed separately here.…”
Section: Resultsmentioning
confidence: 99%
“…That was not what we found in our study, where the form of the brains has shown surprisingly variation among the examined taxa of Characiformes, having provided six phylogenetically useful characters. Thus, the CNS morphology in the Characiformes, as most probably also in other otophysan orders, is unquestionably worth exploring, as was the case for other non-osteological sources for morphological information (e.g., Datovo & Castro, 2012;Datovo & Vari, 2014). was financed by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) and RMCC was financed by Conselho Nacional Desenvolvimento Científico e Tecnológico (CNPq Proc.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two centuries, diagnoses of fish taxa and hypotheses of their evolutionary relationships were almost exclusively based on osteological attributes (see Wiley & Johnson, 2010;Datovo & Vari, 2014). This extensive exploration of osteological features in bony fishes was really efficient in the delimitation of major Teleostei clades; notwithstanding, this almost exclusive focus on osteological features resulted in the "relatively minor attention" to other anatomical systems (Datovo & Vari, 2014), and very few studies have even tried to describe and analyze other major anatomical systems in fishes, such as the neuroanatomy, which according to Datovo & Vari (2014), based mostly on Wiley & Johnson (2010), represents approximately 1% of the synapomorphies currently recognized for teleosteans fishes.…”
Section: Introductionmentioning
confidence: 99%